Kualitas Layanan dan Kemudahan Terhadap Kepuasan Nasabah Menggunakan Aplikasi E-Branch BCA Sebagai Pengganti Slip Manual - Calvin Abimanyu Pramucipta; Savira; Permata Dian Pratiwi (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
The effect of service quality and ease of use of the BCA E-Branch application on customer satisfaction. In the era of rapid digital transformation in the Indonesian banking sector, BCA launched the E-Branch application to facilitate transactions without using manual slips. This study aims to evaluate the impact of the application in the Jabodetabek area, focusing on service quality dimensions including reliability, responsiveness, assurance, empathy, and physical evidence, as well as ease of use including ease of learning, control, flexibility, and clarity. The research method used is a quantitative approach by distributing questionnaires to 187 respondents. The results showed that service quality and ease of use have a significant influence on BCA customer satisfaction in using the E-Branch application. These findings provide important insights for the development of digital services in the banking sector.